Bridging our mandates: evidence-based practice (EBP) and patient-centered care (PCC) 2 - Ratner, Nan Bernstein (Henry Stewart Talks, 2017)
Practice-based evidence (PBE), 'Evidence-farming' (harnessing PBE), Benefits of evidence farming, Outcome due to "good" therapy approaches, Common factors in therapy, Clinician matters as much as the therapy, Factors that tend to enhance patient-centered care, The precarious place of clinical educators